2018
DOI: 10.1021/jacs.8b04638
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Corralled Nanodiscs for the Structural and Functional Characterization of Membrane Proteins and Viral Entry

Abstract: Here we present a modular method for manufacturing large-sized nanodiscs using DNA-origami barrels as scaffolding corrals. Large-sized nanodiscs can be produced by first decorating the inside of DNA barrels with small lipid-bilayer nanodiscs, which open up when adding extra lipid to form large nanodiscs of diameters ~45 or ~70 nm as prescribed by the enclosing barrel dimension. Densely packed membrane protein arrays are then reconstituted within these large nanodiscs for potential structure determination. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…Conversely, molds can block unwanted interactions between independent assemblies. For example, here we show that lipid nanotubes can be templated inside but not outside the barrels, and we recently demonstrated scaffolding of large lipid nanodiscs inside of DNA-origami barrels 35 . This strongly suggests that the DNA barrel can act as a bumper to prevent unwanted aggregation of molecular assemblies hosted on the inside.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Conversely, molds can block unwanted interactions between independent assemblies. For example, here we show that lipid nanotubes can be templated inside but not outside the barrels, and we recently demonstrated scaffolding of large lipid nanodiscs inside of DNA-origami barrels 35 . This strongly suggests that the DNA barrel can act as a bumper to prevent unwanted aggregation of molecular assemblies hosted on the inside.…”
Section: Discussionmentioning
confidence: 61%
“…The cassette was floated in 2 L of reconstitution buffer for 48 h. After dialysis, the sample was recovered from the dialysis cassette and concentrated using an Amicon 30K column. Reconstituted nanostructures were separated from excess lipids by equilibrium centrifugation using iodixanol (Opti-Prep reagent, Sigma-Aldrich) gradient (35,28,18, and 8% from bottom to top). The gradient solutions were layered into ultracentrifuge tubes and centrifuged in Beckman SW41-Ti rotor at 287,730 g (41,000 rpm) for 5 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…These structures have been used for a range of applications. Control of bilayer shape has been used to wrap DNA nanostructures in a protective bilayer to prevent nuclease digestion and increase in vivo circulation time [24] and to assemble 2D DNA lipid 'nanodiscs' for the study of membrane protein interactions [129]. DNA-guided fusion has been used to bypass the endosomal pathway for delivery of proteins into live cells ( Figure 4A) [130] and to assemble biosensors for microRNA detection ( Figure 4B) [131].…”
Section: Bio-inspired Membrane Shapingmentioning
confidence: 99%
“…Multiple copies of these DNA-encircled bilayers can then be scaffolded into a larger DNA ring and fused by modulating detergent concentration to make a large, continuous bilayer of up to 70 nm. Large, DNA-supported 2D bilayers can also be created using this technique by scaffolding and fusing multiple protein lipid nanodiscs inside a DNA origami barrel [129].…”
Section: Directing Liposome Formationmentioning
confidence: 99%
“…By using DNA origami barrelsa ss caffolding corrals,Z hao et al reported a methodt om anufacture larger nanodisks through the assembly of small lipid-bilayern anodisks, which could open up to allow the addition of extra lipids. [44] In such aw ay,n anodisks with diameters as large as 70 nm have been achieved. With the coassembly of VDAC-1 proteins, densely packed membrane protein arrays may also be reconstituted within these large nanodisks.…”
Section: Self-assembly Of Lipids and Membrane Protein Scaffoldedthroumentioning
confidence: 99%